Epigenetic regulation of 11β-hydroxysteroid dehydrogenase type 2 expression - Alikhani-Koopaei, Rasoul (American Society for Clinical Investigation, 2004)
The enzyme 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) is selectively expressed in aldosterone target tissues, where it confers aldosterone selectivity for the mineralocorticoid receptor by inactivating 11β-hydroxyglucocorticoids. Variable activity of 11βHSD2 is relevant for blood pressure control and hypertension. The present investigation aimed to elucidate whether an epigenetic mechanism, DNA methylation, accounts for the rigorous control of expression of the gene encoding 11βHSD2, HSD11B2. CpG islands covering the promoter and exon 1 of HSD11B2 were found to be densely methylated in tissues and cell lines with low expression but not those with high expression of HSD11B2. Demethylation induced by 5-aza-2′-deoxycytidine and procainamide enhanced the transcription and activity of the 11βHSD2 enzyme in human cells in vitro and in rats in vivo. Methylation of HSD11B2 promoter–luciferase constructs decreased transcriptional activity. Methylation of recognition sequences of transcription factors, including those for Sp1/Sp3, Arnt, and nuclear factor 1 (NF1) diminished their DNA-binding activity. Herein NF1 was identified as a strong HSD11B2 stimulatory factor. The effect of NF1 was dependent on the position of CpGs and the combination of CpGs methylated. A methylated-CpG–binding protein complex 1 transcriptional repression interacted directly with the methylated HSD11B2 promoter. These results indicate a role for DNA methylation in HSD11B2 gene repression and suggest an epigenetic mechanism affecting this gene causally linked with hypertension.